Teste de envelhecimento acelerado em sementes de quiabo - Lopes, Magnolia de Mendonca [UNESP] (2010)
The objective of this research was to study the accelerated aging test to evaluate the okra vigor seed. Were used four okra seed lots cv. "Santa Cruz". The initial seed lot quality was evaluate by the moisture content, germination, first germination count, speed of germination index and seedling emergence. The experiment was carried out in two phases: the first one the seeds were submitted to the accelerate aging with and without NaCl salt solution aging periods of 48, 72, 96 and 120 hours, at 41 and 45(0) C temperature. The second phase the best procedures as for as accelerated aging and temperatures were repeated. The period of 72h and 41 C with and without NaCl saturated solution was the most adequate for the lot classification in distint vigor levels.